2019
DOI: 10.1177/0269216318824276
|View full text |Cite
|
Sign up to set email alerts
|

Common dedication to facilitating good dying experiences: Qualitative study of end-of-life care professionals’ attitudes towards voluntary assisted dying

Abstract: Background:Debate about appropriate and ethically acceptable end-of-life choices is ongoing, which includes discussion about the legalization of voluntary assisted dying. Given health professionals’ role in caring for patients at the end life, their stance towards assisting a person with dying can have implications for policy development and implementation in jurisdictions where law changes are being considered.Aim:To explore end-of-life care professionals’ attitudes towards voluntary assisted dying 6 months p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 24 publications
3
28
0
1
Order By: Relevance
“…Most of the empirical studies examining CO occur in the context of abortion. The limited empirical studies that have examined why health practitioners may be opposed to euthanasia/assisted dying (not necessarily defined as a CO) have found that opposition arises from a variety of sources including: concern about being unable to cope emotionally (Otte et al 2017); incompatibility with the ethos of the medical profession (Otte et al 2017); incompatibility with one's personal and moral beliefs (Turla et al 2007;Otte et al 2017); disagreement with interfering with death (Clark et al 2001;Blaschke et al 2019); the potential for abuse amongst vulnerable populations (Clark et al 2001); and viewing palliative care as a better alternative (Clark et al 2001;Blaschke et al 2019).…”
Section: Vad In Victoriamentioning
confidence: 99%
“…Most of the empirical studies examining CO occur in the context of abortion. The limited empirical studies that have examined why health practitioners may be opposed to euthanasia/assisted dying (not necessarily defined as a CO) have found that opposition arises from a variety of sources including: concern about being unable to cope emotionally (Otte et al 2017); incompatibility with the ethos of the medical profession (Otte et al 2017); incompatibility with one's personal and moral beliefs (Turla et al 2007;Otte et al 2017); disagreement with interfering with death (Clark et al 2001;Blaschke et al 2019); the potential for abuse amongst vulnerable populations (Clark et al 2001); and viewing palliative care as a better alternative (Clark et al 2001;Blaschke et al 2019).…”
Section: Vad In Victoriamentioning
confidence: 99%
“…From June 19, 2019, Victorians who are at the end of life and comply with strict criteria, can request physicians to prescribe a lethal dose of medication for them to ingest, or in limited circumstances, request physician assistance to administer a lethal substance. 3 In Victoria, VAD means 'the administration of a VAD substance and includes steps reasonably related to such administration. ' 4 The Victorian Act allows adult Australian citizens or permanent residents, currently resident in Victoria, having decision-making capacity, in the final weeks or months of life, with a serious and incurable condition causing enduring and unbearable suffering that cannot otherwise be adequately relieved to choose the option of VAD.…”
Section: Introductionmentioning
confidence: 99%
“…4 Consequently there is limited local data available to inform hospital approaches to implementation despite the shared goal of reducing suffering and providing good dying experiences for patients. 3,5,6 The experiences of clinicians in other jurisdictions have been mixed, with some experiencing considerable difficulties in working relationships, [7][8][9] whilst others found that relationships with colleagues could also be strengthened 7 . For some there was a lack of clarity in their role and scope of practice.…”
Section: Introductionmentioning
confidence: 99%
“…Some participants perceived MAiD to be broadly permissible and raised concerns about its practical consequences, 53 since different responses exist for multifaceted sources, expressions, or experiences of suffering. 43 , 54 , 55 They reported that most enquiring patients did not have severe refractory physical symptoms that required medical interventions.…”
Section: Discussionmentioning
confidence: 99%